PENERAPAN PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH DI SEKOLAH DASAR - Fabianus Hadiman Bosco; Abdul Madjir; Anderianus Bandur (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
The Aim of this research is to get to know and elucidate the implementation of character education over and done with school culture in elementary school.This enquiry is motivated by an educational process which is not in agreement with the existed school culture, such as regulations and character values ​​that existed but the procedure of implementing is not optimum. The directions and personality values which are in the application process is not optimal are: founded an elementary school students who did not respond to the numerous activities organized by the school, the students are lacking of disciplinary, the students are lacking of enthusiasm to the activities organized by the school and in implementing school culture still depends on the leadership style of the principle.The method that is used in this study is a qualitative method with the object of literature study. The technique that is used for data collection in this research is observation, wherein the data collection attained by examining books, journals, theses, articles, and the theses that are used as sources.The data in this study are analyzed by data reduction, data presentation, and verification or getting the inference.The pertinent of the research upshot shows that the implementation of character education through school culture in elementary schools has been well implemented by getting familiar the existing character values. The author supports the fallouts of this enquiry because by familiarize the character values ​​in the school it will have a positive bearing on the personalitiesof the students, especially if the habituation is carried out uninterruptedly in the school milieu. The character values ​​that can be formed through school culture are religiosity, discipline, responsibility, caring with the milieu, and loving the homeland.Grounded on the foretold narrative it can be summed up that the teacher had implemented the character education over school culture.